Caterpillar saliva interferes with induced Arabidopsis thaliana defence responses via the systemic acquired resistance pathway - Weech, Marie-Hélène; Chapleau, Mélanie; Pan, Li; Ide, Christine; Bede, Jacqueline C (Journal of experimental botany, 2008)
Arabidopsis thaliana (L.) Heynh. genotypes limited in their ability to mount either octadecanoid-dependent induced resistance (IR⁻) or systemic acquired resistance (SAR⁻) were used to characterize the roles of these pathways in plant-herbivore interactions. Molecular and biochemical markers of IR were analysed in plants subject to herbivory by caterpillars of the beet armyworm, Spodoptera exigua Hübner, which had either intact or impaired salivary secretions since salivary enzymes, such as glucose oxidase, have been implicated in the ability of caterpillars to circumvent induced plant defences. Transcript expression of genes encoding laccase-like multicopper oxidase [AtLMCO4 (polyphenol oxidase)] and defensin (AtPDF1.2) showed salivary-specific patterns which were disrupted in the SAR⁻ mutant plants. The activity of octadecanoid-associated anti-nutritive proteins, such as LMCO and trypsin inhibitor, showed similar patterns. Gene and protein changes parallel plant hormone levels where elevated jasmonic acid was observed in wild-type plants fed upon by caterpillars with impaired salivary secretions compared with plants subject to herbivory by normal caterpillars. This salivary-specific difference in jasmonic acid levels was alleviated in SAR⁻ mutants. These results support the model that caterpillar saliva interferes with jasmonate-dependent plant defences by activating the SAR pathway.